2016
DOI: 10.1016/j.chemosphere.2015.12.072
|View full text |Cite
|
Sign up to set email alerts
|

Photodecomposition of tetrabromobisphenol A in aqueous humic acid suspension by irradiation with light of various wavelengths

Abstract: The reactive species generated in aqueous 3,3',5,5'-tetrabromobisphenol A (TBBPA)/humic acid (HA) suspensions above the TBBPA pKa (∼7.4), under various light-irradiation conditions, namely ambient and ultraviolet light, were investigated using electron paramagnetic resonance (EPR) spectroscopy and liquid chromatography-mass spectrometry (LC-MS). We confirmed that singlet oxygen and OH radicals are the key reactive oxygen species generated at wavelengths greater than 400 and 300 nm, respectively. The amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Some of the commonly used NBFRs include decabromodiphenyl ethane or 1,2bis(pentabromodiphenyl)ethane (DBDPE), 1,2-bis(2,4,6-tribromophenoxy)ethane (BTBPE), 2-ethylhexyl-2,3,4,5-tetrabromobenzoate (TBB or EHTBB), bis(2ethylhexyl)-3,4,5,6-tetrabromo-phthalate (TBPH or BEHTBP), tetrabromobisphenol Abis(2,3-dibromopropylether) (TBBPA-DBPE) and tetrabromobisphenol A bis (allyl) ether (TBBPA-BAE). At present, the most widely used BFR is TBBPA (50% of BFRs currently used) with an estimated annual production volume of 130.000 tons (Han et al, 2016). TBBPA-containing materials are used in the manufacturing of office and home electronic equipment, such as computer printed circuit boards, mobile phones, televisions, washing machines, etc.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some of the commonly used NBFRs include decabromodiphenyl ethane or 1,2bis(pentabromodiphenyl)ethane (DBDPE), 1,2-bis(2,4,6-tribromophenoxy)ethane (BTBPE), 2-ethylhexyl-2,3,4,5-tetrabromobenzoate (TBB or EHTBB), bis(2ethylhexyl)-3,4,5,6-tetrabromo-phthalate (TBPH or BEHTBP), tetrabromobisphenol Abis(2,3-dibromopropylether) (TBBPA-DBPE) and tetrabromobisphenol A bis (allyl) ether (TBBPA-BAE). At present, the most widely used BFR is TBBPA (50% of BFRs currently used) with an estimated annual production volume of 130.000 tons (Han et al, 2016). TBBPA-containing materials are used in the manufacturing of office and home electronic equipment, such as computer printed circuit boards, mobile phones, televisions, washing machines, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been found in exposed humans and animals and was reported to be neurotoxic and endocrine disruptor (Jakobsson et al, 2002;Cariou et al, 2008;Van der Ven et al, 2008;Geens et al, 2009;Dourson, 2015;Liu et al, 2016;Gong et al, 2017;Inthavong et al, 2017). Various studies have investigated the transformation pathways of TBBPA in the environment, in particularly photodegradation in surface water (Eriksson et al, 2004b;Wang et al, 2015b;Han et al, 2016). Direct photolysis of TBBPA under solar irradiation was found to occur in aqueous solution and via photosensitized reactions with OH radicals and singlet oxygen generated by irradiation of humic substances (Eriksson et al, 2004b;Han et al, 2009;Wang et al, 2015b;Han et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A small number of studies have focused on the photodegradation of TBBPA via $OH and 1 O 2 (Eriksson et al, 2004;Bao and Niu, 2015;Wang et al, 2015b;Han et al, 2016). Wang et al (2015b) reported that the photolysis of TBBPA could occur with 1 O 2 in an aqueous solution under simulated-solar-light irradiation.…”
Section: Introductionmentioning
confidence: 99%